Hakikat Ilmu Pengetahuan dalam Perspektif Modern dan Islam - Siswati, Via Linda (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
Philosophy of science is a branch of philosophy that reflects, radically and integral about the nature of knowledge itself. This writing aims to understand: (1) understanding of knowledge and science in etymology and terminology. (2) the difference of science, knowledge and religion in epistimology. (3) the extent of science in Islam. (4) the basic characteristics of science. (5) truth theory. (6) sources of knowledge. (7) the boundaries of science (8) the structure of knowledge. The results of this paper are: (1) science is from Arabic, 'alima. The meaning of this word is knowledge. And science in terminology is the whole conscious effort to investigate, find, and improve human understanding from various aspects of reality in human nature and we know (2) The location of the difference is the science is a summary of a collection of knowledge or the result of knowledge and facts, The order of faith or order of belief in the existence of something absolute outside man, in accordance and in line with the order of faith and order of worship. (3) The principal features of science are as follows: (a) Systematic, (b) Authenticity, (c) Rationality, (d) Objectivity, (e) Verifiability, (f) Communality. (4) The theory in a theory of truth there are 3 namely: Correspondence Theory, Coherence Theory, Theory of Pragmatism. (4) The source of human knowledge uses two ways of obtaining correct knowledge, first through rationality and secondly through experience. (5) Science limits its exploration to human experience, hence science begins on exploration of human experience and ceases to human experience, and that is the limit of knowledge. (6) Science is essentially a collection of knowledge that explains the various natural phenomena that allow humans to perform a series of actions to master these symptoms based on existing explanations.